La medida cautelar del apremio personal no garantiza el pago de las pensiones alimenticias dejando en la desprotección a los menores que reciben una pensión alimenticia atentando en forma directa a su desarrollo integral - Castillo Córdova, Wilmer Emilio (2015)
This paper grade has its origin with the problem that exists with food debtors having no debt workout as the judge instructs the staff urge against the debtor for leading food and profit. It has made the investigation and prosecution of legal doctrine and bibliographic information. A theoretical framework and conducted a critical analysis on the right doctrinal synthesis of food throughout history, also with regard to maintenance benefits in the constitutions of Ecuador was prepared , plus an analysis of the second book Professional Title V code children and adolescents and to complete a short survey on the various international treaties and agreements concerning the subject. To determine this issue a diagnosis was made by applying the three research techniques with an observation hundred fifteen field trials in the food court files of childhood and adolescence the provincial court of Santo Domingo in 2012 and consequently quantified the number of orders or personal urge that these arguments have been obligated in arrears in the payment of alimony ` in the same period of time. Applies interview and structured survey of five experts headed right to survey twenty users of the judicial function of Santo Domingo de los Tsachilas The project consists of a substantive and procedural rules of an alternative measure personal urgency for late alimony payment when required without financial resources and achieving the proposed amendment to art. And Article 22 of the Code enumerated in children and adolescents for the purpose of inserting the debtor alimony unemployed are within a temporary worker program. Impacts rights that generated the project developed techniques, THROUGH indications as greater or lesser impact on both the socio-cultural, educational, legal and technical studies are determined. At the completion of the project is prayer that creates the conditions and recommendations have been drafted based on all information gathered throughout the development that gender Work degree. This thesis entitled “THE PRECAUTIONARY MEASURE OF PERSONAL URGED NOT WARRANT THE PAYMENT OF MAINTENANCE PAYMENTS ON LEAVING DEPROTECTION CHILDREN RECEIVING A PENSION ATTEMPTING FOOD DIRECTLY TO YOUR INTEGRAL DEVELOPMENT” the obligor "is a legal problem daily it has been facing in the courts of childhood and adolescence , where the obligor who is deprived of his liberty by staff urgency once he regains his freedom, was arrested with another ballot personal restraint for alimony arrears , not the could pay , because of en contrase arrested days defined Listed Art . 141…22 of the Code on Children and Adolescents. This procedural flaw of the food trial , violates the right of the obligor to not allow you to work and infringes the right of the feed , because should continue longer, waiting for the obligor to recover their freedom and achieve work and pay alimony